How not to talk about it: Using digital storytelling with children with anxiety - Diane Macdonald; Chloe Watfern; Katherine M Boydell (Methods in Psychology)
This paper explores the benefits and challenges of using digital storytelling (DST) in mental health research with children. By using DST to centre children's experiences, the study empathetically deepens our understanding of children's complex mental health issues. DST involves a gradual process that fosters safe self-expression and imaginative storytelling. The DST process can help convey difficult or stressful stories coherently and creatively to support both researchers and participants in understanding mental health issues. However, a narrow focus on neat endings and resolutions may limit authentic expression, indicating a need for more open-ended narrative structures to capture the complexities of children's mental health experiences.This is a story about three stories. This is also a story about the discoveries and challenges of working alongside children (ages 10–13) as they used digital storytelling to share their anxiety experiences through short self-made videos. Our journey began with two questions: How would children portray their anxiety through digital storytelling? What aspects of the digital storytelling process would be the most fruitful for both participants and researchers, and why? In this paper, we weave three of the children's stories within our own narrative of using digital storytelling as a research tool to better understand children's experiences of anxiety. Rather than present the children's stories as the results of our research, we use their stories as springboards for articulating and interrogating digital storytelling as a tool for understanding anxiety. We intertwine the first-person accounts of each child with our academic prose, deliberately highlighting the different ways of knowing that our approach enables.